Diaphragmatic Myopotential Oversensing Caused by Change in Implantable Cardioverter Defibrillator Sensing Bandpass Filter. Issue 7 (31st March 2016) - PLOUX, SYLVAIN; SWERDLOW, CHARLES D.; ESCHALIER, ROMAIN; MONTEIL, BENJAMIN; OUALI, SANA; HAÏSSAGUERRE, MICHEL; BORDACHAR, PIERRE
Abstract : Diaphragmatic myopotential oversensing (DMO) causes inhibition of pacing and inappropriate detection of ventricular fibrillation in implantable cardioverter defibrillators (ICDs). It occurs almost exclusively with integrated bipolar leads and is extremely rare with dedicated bipolar leads. If DMO cannot be corrected by reducing programmed sensitivity, ventricular lead revision is often required. The new Low Frequency Attenuation (LFA) filter in St. Jude Medical ICDs (St. Jude Medical, Sylmar, CA, USA) alters the sensing bandpass to reduce T‐wave oversensing. This paper aims to present the LFA filter as a reversible cause of DMO. Unnecessary lead revision can be avoided by the simple programming solution of deactivating this LFA filter.